The Indonesian way ASEAN, Europeanization, and foreign policy debates in a new democracy - Rüland, Jürgen 1953- (Studies in Asian security, 2018)
This book traces how ideas of regional integration have traveled from Europe to Indonesia, and how Indonesian foreign policy stakeholders have reinterpreted these ideas